(3GdfXGe GdEOGQi HGdeedcI GdYQHjI GdSYhOjI Hjf GdeQcRjI GdEOGQjI GdcGedI h Hjf GddGeQcRjI GdEOGQjI GdeYJOdI (B/ s - (3eMeO Hf Ydi eMeO GdbMWGfis; (3eMeO eMeO HOQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JOhQ gPg GdOQGSI dHjGf eOi JWHjb GddGeQcRjI ai GdeedcI GdYQHjI GdSYhOjI(B: (3h bO JhUdJ GdOQGSI Gf gfGc NWhGJ fMh JWHjb GddGeQcRjI(B: (3GdG Gfg JhLO YKQGJ ef GdfGMjI GdJWHjbI GhVMJgG GdOQGSI(B: (3h dbO JhUdJ GdOQGSI dYOO ef GdfJGFL h GdJhUjGJ GdJj JgOa Gdj JaYjd OhQ GddGeQcRjI GdGOGQjI deG dgG ef OhQ cHjQ ai JMbjb GdJfejI HTJi UhQgG(B: (3h dG jYfi gPG GdGSJZfGA Yf GdeQcRjI HUag YGeI(B: (3h GfeG JgOa GdOQGSI Gdi JWHjb GddGeQcRjI GdGOGQjI GVGaI Gdi GdeQcRjI GdSjGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B251-286s
Keywords: (3GdbGfhf GdYGes; (3GdeedcI GdYQHjI GdSYhOjIs; (3SdWGJ Gdedcs; (3GNJUGUGJ Gdedcs; (3GdJahjVs; (3fXGe GdebGWYGJs; (3GdeLGdS GdHdOjIs; (3fXGe GdefGWbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes